Comprehensive Assessment of BARD1 Messenger Ribonucleic Acid Splicing With Implications for Variant Classification - Walker, Logan C.; Lattimore, Vanessa Lilian; Kvist, Anders; Kleiblova, Petra; Zemankova, Petra; de Jong, Lucy; Wiggins, George A. R.; Hakkaart, Christopher; Cree, Simone L.; Behar, Raquel; Houdayer, Claude; Investigators, kConFab; et al. (Frontiers in Genetics, 2019)
Introduction Case–control analyses have shown BARD1 variants to be associated with up to >2-fold increase in risk of breast cancer, and potentially greater risk of triple negative breast cancer. BARD1 is included in several gene sequencing panels currently marketed for the prediction of risk of cancer, however there are no gene-specific guidelines for the classification of BARD1 variants. We present the most comprehensive assessment of BARD1 mRNA splicing, and demonstrate the application of these data for the classification of truncating and splice site variants according to American College of Medical Genetics and Genomics and the Association for Molecular Pathology (ACMG/AMP) guidelines. Methods Nanopore sequencing, short-read RNA-seq (whole transcriptome and targeted), and capillary electrophoresis analysis were performed by four laboratories to investigate alternative BARD1 splicing in blood, breast and fimbriae/ovary related specimens from non-cancer affected tissues. Splicing data were also collated from published studies of nine different tissues. The impact of the findings for PVS1 annotation was assessed for truncating and splice site variants. Results We identified 62 naturally occurring alternative spliced BARD1 splicing events, including 19 novel events found by next generation sequencing and/or RT-PCR analysis performed for this study. Quantative analysis showed that naturally occurring splicing events causing loss of clinically relevant domains or nonsense mediated decay can constitute up to 11.9% of overlapping natural junctions, suggesting that aberrant splicing can be tolerated up to this level. Nanopore sequencing of whole BARD1 transcripts characterised 16 alternative isoforms from healthy controls, revealing that the most complex transcripts combined only two alternative splice events. Bioinformatic analysis of ClinVar submitted variants at or near BARD1 splice sites suggest that all consensus splice site variants in BARD1 should be considered likely pathogenic, with the possible exception of variants at the donor site of exon 5. Conclusions No BARD1 candidate rescue transcripts were identified in this study, indicating that all premature translation-termination codons variants can be annotated as PVS1. Furthermore, our analysis suggests that all donor and acceptor (IVS+/-1,2) variants can be considered PVS1 or PVS1_strong, with the exception of variants targeting the exon 5 donor site, that we recommend considering as PVS1_moderate.